2018
DOI: 10.20944/preprints201811.0237.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Erythrocyte n-6 Fatty Acids and Risk for Cardiovascular Outcomes and Total Mortality in the Framingham Heart Study

Abstract: Background: The prognostic value of erythrocyte levels of the n-6 fatty acids (FAs) for total mortality and cardiovascular disease (CVD) outcomes remains an open question. Methods: We examined CV outcomes and death in 2500 individuals in the Framingham Heart Study Offspring cohort without prevalent CVD (mean age 66 years, 57% women) as a function of baseline levels of different length n-6 FAs (18 carbon, 20 carbon and 22 carbon) in the erythrocyte membranes. Clinical outcomes were monitored for up to 9.5 years… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…Our MR study suggests genetically predicted plasma phospholipid AA is associated with ASCVD (IHD, stroke and possibly PAD) and VTE, but not with other CVDs, independent of the Flores haplotype rs174547, with possibly a stronger association for ASCVD in men than women. These findings are consistent with some [ 18 ], [ 46 ] but not all [ [15] , [16] , [17] ], [ 19 ] observational studies of the association of circulating or tissue AA with ASCVD or its subtypes but add by providing an estimate less open to residual and unmeasured confounding. Our findings add to previous MR studies by using larger GWASs, assessing the associations with a wider range of CVDs, and distinguishing effects of AA from effects of the highly pleiotropic Flores haplotype [ 25 ], [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our MR study suggests genetically predicted plasma phospholipid AA is associated with ASCVD (IHD, stroke and possibly PAD) and VTE, but not with other CVDs, independent of the Flores haplotype rs174547, with possibly a stronger association for ASCVD in men than women. These findings are consistent with some [ 18 ], [ 46 ] but not all [ [15] , [16] , [17] ], [ 19 ] observational studies of the association of circulating or tissue AA with ASCVD or its subtypes but add by providing an estimate less open to residual and unmeasured confounding. Our findings add to previous MR studies by using larger GWASs, assessing the associations with a wider range of CVDs, and distinguishing effects of AA from effects of the highly pleiotropic Flores haplotype [ 25 ], [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…Observational findings concerning circulating or tissue levels of AA are mixed, with some studies suggesting no association with CVD [ [15] , [16] , [17] ], one showing a positive association with myocardial infarction [ 18 ], and another suggesting an inverse association with coronary events [ 19 ]. No obvious difference by sex has been observed [ 15 ], [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the n -6 series of FAs did not affect variables related to biochemistry and blood pressure in a meta-analysis of four randomized primary prevention studies, which included 660 individuals followed for 24 weeks [ 24 ]. Moreover, Harris et al [ 25 ] examined cardiovascular outcomes and death after a median of 7 years of follow-up of 2500 individuals with a mean age of 66 years in the Framingham Heart Study Offspring cohort without prevalent CVD, and found no association between the content of n -6 FAs in erythrocytes and total deaths, and no association with cardiovascular events. Reasons for heterogeneity in the results between these studies may be the clinical setting (primary versus secondary prevention) and age difference, and perhaps, also different diets.…”
Section: Discussionmentioning
confidence: 99%
“…Unbestritten bleibt jedoch, dass die physiologische Zufuhr von langkettigen Omega-3-Fettsäuren, bspw. als schonend zubereiteter Meeresfisch, mit einer reduzierten kardiovaskulären Mortalität assoziiert ist 5 .…”
Section: Studien-kommentarunclassified